Philippines 2007 National Transfer Accounts: Consumption, Income, and Intergenerational Reallocation of Resources - Revised Estimates - J.M. Ian S. Salas; Michael Ralph M. Abrigo; Rachel H. Racelis (Philippine Institute for Development Studies (PIDS), 2012)
This paper describes the revised national level estimates of the 2007 Philippines NTA. The differences between the previous and the revised 2007 Philippines NTA Flow Accounts estimates are due to the change in the treatment of overseas Filipino workers' (OFW) remittances: treated as interhousehold transfers in the previous estimates; and treated mainly as labor income (earnings) in the revised estimates. The main changes in the estimates and results are those related to labor income and lifecycle deficit including: (1) the peak ages in per capita earnings and self-employment are both lower by one year at 28 years (previously 29 years) and 44 years (previously 45 years), respectively; (2) lifecycle deficit age cut-off are 24 years (previously 25 years) for the young and 59 years (previously 58 years) for the elderly; and (3) there is negative lifecycle deficit (i.e., there is surplus) for ages 25-58 years (previously 26-57 years).
Keywords: 330; Philippines; National Transfer Accounts; economic lifecycle; intergenerational transfer; consumption age profile; lifecycle deficit; labor income age profile